Appearance structural member and electronic equipment

By adopting a double-layer stacked structure design in metal parts, hot-rolled composite of high-purity non-recycled aluminum alloy material and recycled aluminum alloy material, the problem of appearance defects after anode treatment is solved, and the utilization rate and material of recycled materials are improved The mechanical properties of the high-strength aluminum alloy material can be effectively recovered and utilized.

CN222216222UActive Publication Date: 2024-12-20LENOVO (BEIJING) LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420646000.8
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2024-12-20
Estimated Expiration
2034-03-29

AI Technical Summary

Technical Problem

After the anode treatment, metal parts are prone to appearance defects, such as material textures and black spots, which affect their application, especially in the recycling and utilization of high-strength aluminum alloy materials. Impurities affect the appearance and lead to unqualified appearance, limiting the recycling rate of materials. .

Method used

Using a double-layer stacked structure design, one of which is a high-purity non-recycled aluminum alloy material as the appearance layer, and the other is a recycled aluminum alloy material. Through the use of hot-rolled composite and aluminum strip layer, a tightly bonded alloy layer is formed to reduce the Defects during anode treatment and improve material recycling rate.

Benefits of technology

It effectively avoids appearance defects after anode treatment, increases the proportion of recycled materials, reaches more than 60%, reduces development costs, and improves the versatility and mechanical properties of materials, meeting the appearance needs of high-strength aluminum alloy materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222216222U_ABST
    Figure CN222216222U_ABST
Patent Text Reader

Abstract

The utility model relates to the technical field of appearance structural parts, and provides an appearance structural part which comprises a first structural layer and a second structural layer. The first structure layer comprises a first surface and a second surface; the appearance of the first surface is not changed after the first surface is subjected to anodic treatment; and the second surface is in contact connection with one surface of the second structure layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic equipment, and in particular to an appearance structural component and an electronic equipment. Background Art

[0002] Products with metal appearance are becoming more and more popular among consumers due to their exquisite appearance, strong durability, good heat dissipation performance and good signal reception.

[0003] Metals generally need to be anodized for appearance. Anodizing, also known as anodic oxidation, is a metal surface treatment technology that uses electrolyte and DC power to form an oxide film on the metal surface, thereby enhancing the metal's corrosion resistance, hardness, wear resistance, insulation and heat resistance. In addition, anodizing can also improve the appearance of metal parts. For example, by changing the electrolyte and voltage conditions, oxide films of different colors can be formed on the surface of metal products, which has both decorative and protective effects.

[0004] However, after anodizing, metal parts will have defects of varying degrees on the surface, such as material lines, black spots, etc., which affect the application of metal parts. Utility Model Content

[0005] In view of this, the technical problem to be solved by the present application is to provide an appearance structural part and an electronic device, wherein the appearance structural part has no defects in appearance after anodizing.

[0006] The present application provides an appearance structural member, comprising a first structural layer and a second structural layer;

[0007] The first structural layer comprises a first surface and a second surface; the appearance of the first surface does not change after anodizing;

[0008] The second surface is in contact with and connected to a surface of the second structural layer.

[0009] Optionally, the first structural layer and the second structural layer are respectively made of aluminum alloy materials with different purities, and the material purity of the first structural layer is greater than the material purity of the second structural layer.

[0010] Optionally, the thickness of the first structural layer is 0.05-0.2 mm;

[0011] The thickness of the second structural layer is 0.5-1.0 mm.

[0012] Optionally, an aluminum tape layer with a double-sided roughened structure is arranged between the first structural layer and the second structural layer; the roughened structure is fused with the first structural layer and the second structural layer respectively to fasten the two.

[0013] Optionally, the second surface of the first structural layer is provided with a roughened structure, and the roughened structure is fused with the second structural layer to fasten the two;

[0014] Alternatively, a surface of the second structural layer in contact with the first structural layer is provided with a textured structure, and the textured structure is fused with the second surface of the first structural layer to fasten the two.

[0015] Optionally, the texturing structure is arranged in multiple rows.

[0016] Optionally, the roughened structure is one or more of needle-shaped burrs, conical burrs, round protrusions, columnar protrusions, and irregular protrusions.

[0017] Optionally, the height of the roughened structure is 0.001-0.002 mm.

[0018] Optionally, the surface of the hairy structure is a roughened surface.

[0019] The present application provides an electronic device, including:

[0020] An appearance structural part, the appearance structural part comprises a first structural layer and a second structural layer, the first structural layer comprises a first surface and a second surface; the appearance of the first surface does not change after anodizing, and the second surface is in contact with and connected to a surface of the second structural layer;

[0021] ontology;

[0022] The appearance structural component wraps at least one surface of the body, and the first surface is an outer surface of the wrapped surface.

[0023] Compared with the prior art, the present application provides an appearance structural part, including a first structural layer and a second structural layer; the first structural layer includes a first surface and a second surface; the appearance of the first surface does not change after anodizing; the second surface is in contact and connected with a surface of the second structural layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the structure of the appearance structural parts provided for this application;

[0025] Figure 2 It is a schematic diagram of a container divided into two chambers A and B by an aluminum strip;

[0026] Figure 3 This is a schematic diagram of the concave-convex matching of the roughened structure;

[0027] Figure 4 It is a schematic diagram of the concave and convex coordination of the roughened structure. DETAILED DESCRIPTION

[0028] The present application provides an appearance structural member, comprising a first structural layer and a second structural layer;

[0029] The first structural layer comprises a first surface and a second surface; the appearance of the first surface does not change after anodizing;

[0030] The second surface is in contact with and connected to a surface of the second structural layer.

[0031] Figure 1 This is a schematic diagram of the structure of the appearance structural member provided in the present application, wherein A is the first structural layer, B is the second structural layer. The side of the first structural layer away from the second structural layer is the first surface, and the side in contact with the second structural layer is the second surface.

[0032] The first surface is the appearance part of the appearance structural component, and the second structural layer is the non-appearance part of the appearance structural component.

[0033] The present application adopts a double-layer laminated structure design, and the appearance of the part does not change after anodizing, and there will be no defects such as texture and black spots, so that the appearance of the product maintains good aesthetics after anodizing.

[0034] In some specific embodiments, the first structural layer and the second structural layer are made of materials with different purities.

[0035] In some specific embodiments, the first structural layer and the second structural layer are made of metal materials with different purities.

[0036] In some specific embodiments, the first structural layer and the second structural layer are respectively made of aluminum alloy materials with different purities.

[0037] The above double-layer stacked structure design can reduce the purity requirement for the second structural layer material.

[0038] In some specific embodiments, the material purity of the first structure layer is greater than the material purity of the second structure layer.

[0039] In some specific embodiments, the material of the first structural layer is a non-recycled material, and the purity thereof is 100%.

[0040] The above 100% purity means that no impurities are introduced into the material. Taking aluminum alloy material as an example, its purity of 100% means that no other impurities are introduced except the aluminum alloy component.

[0041] In some specific embodiments, the material of the second structural layer is recycled material. The present application has no special limitation on the source of the recycled material, and general recycled materials are acceptable, and the purity of the material is above 80%.

[0042] The purity of the above-mentioned recycled materials refers to: 100% - the mass content of impurities in the recycled materials.

[0043] At present, a large amount of waste materials lack effective recycling and utilization, which has caused great waste and damage to the environment and resources. Especially aluminum alloy materials, the aluminum alloy materials 5052, 5L52, 5H85, 5H59 and other high-strength aluminum alloy materials that are often recycled are affected by impurities. After the aluminum alloy is recycled and anodized, there will be defects of varying degrees in appearance, such as material lines, black spots, etc., which cannot meet the appearance requirements. At present, in the preparation of high-strength aluminum alloy materials, such as 5H59 materials, the proportion of recycled aluminum alloy materials is only about 55%, and the proportion of recycled aluminum alloy materials in silk aluminum 5L52 is only about 20%. If it is higher, the appearance will not meet the requirements. This greatly restricts the recycling rate of materials.

[0044] This application uses the above-mentioned laminated structural design to compound non-recycled materials on the outside of recycled materials as an appearance layer, ensuring that the product appearance has no defects and that the material surface is not affected by impurities in the recycled materials. This greatly increases the proportion of recycled materials in the material, making the proportion of recycled materials reach more than 60%, which can reduce development costs, have the same development cycle as normal materials, and have stronger versatility.

[0045] In some specific embodiments, the material of the first structural layer is non-recycled aluminum alloy material.

[0046] In some specific embodiments, the material of the second structural layer is recycled aluminum alloy material.

[0047] Optionally, the purity of the aluminum alloy material of the second structural layer is above 80%.

[0048] The present application does not specifically limit the source of the above-mentioned recycled aluminum alloy material, and general recycled aluminum alloy materials can be used.

[0049] In some specific embodiments, the thickness of the first structural layer is 0.05-0.2 mm.

[0050] In some specific embodiments, the thickness of the first structural layer is 0.1 mm.

[0051] The thickness of the second structural layer is not limited and can be set according to actual needs.

[0052] In some specific embodiments, the thickness of the second structural layer is 0.5-1.0 mm.

[0053] In some specific embodiments, the thickness of the second structural layer is 0.5-0.7 mm.

[0054] The first structural layer and the second structural layer can be combined by hot rolling. During the hot rolling process, the materials are rolled up and down to combine, the contact layers penetrate each other, aluminum molecules diffuse at the contact surface of the first structural layer and the second structural layer, and an alloy layer is formed at the bonding surface to combine the two.

[0055] In order to improve the bonding degree between the first structural layer and the second structural layer in the above-mentioned appearance structural member, an aluminum strip layer is arranged between the first structural layer and the second structural layer.

[0056] The aluminum strip layer may have a smooth surface, a rough surface, or a roughened structure, which serves to increase the contact area and make the combination of the two more secure.

[0057] The rough surface and the textured structure may be arranged on one side or both sides of the aluminum strip layer.

[0058] In some specific embodiments, a container is provided, which is divided into two chambers A and B by an aluminum strip. Molten casting liquid A and casting liquid B are added to chambers A and B respectively. The temperature of the casting liquid causes the aluminum strip to fuse with casting liquid A and casting liquid B respectively, and the above-mentioned appearance structural parts are formed after cooling.

[0059] The casting liquid A and the casting liquid B are raw materials for forming the first structural layer and the second structural layer respectively.

[0060] Figure 2 This is a schematic diagram of the container being divided into two chambers A and B by an aluminum strip.

[0061] In some specific embodiments, the aluminum tape layer is provided with a roughened structure.

[0062] In some specific embodiments, the roughened structure is provided on both sides, and the roughened structure is fused with the first structural layer and the second structural layer respectively to fasten the two.

[0063] In some specific embodiments, a container is provided, which is divided into two chambers A and B by an aluminum strip with a double-sided texturized structure. Molten casting liquid A and casting liquid B are added into chambers A and B respectively. The temperature of the casting liquid causes the aluminum strip with the texturized structure to fuse with casting liquid A and casting liquid B, and the above-mentioned appearance structural parts are formed after cooling.

[0064] In some specific embodiments, the textured structure of the aluminum tape layer is disposed on a single surface.

[0065] In some specific embodiments, a container is provided, which is divided into two chambers A and B by an aluminum strip having a single-sided roughened structure. Molten casting liquid A and casting liquid B are added into chambers A and B respectively. The temperature of the casting liquid causes the roughened structure of the aluminum strip to fuse with the casting liquid on the same side, and the above-mentioned appearance structural parts are formed after cooling.

[0066] The shape of the container can be set according to the shape of the appearance structural member. Optionally, the container is in a cubic shape and is hollow.

[0067] In some specific embodiments, the textured structure is disposed on the contact surface between the first structural layer and the second structural layer.

[0068] The above solution saves the use of aluminum strip layers and further saves raw materials. At the same time, the workpiece is changed from two contact surfaces formed by the aluminum strip layer and the first structural layer and the second structural layer respectively to only one contact surface between the first structural layer and the second structural layer, which can further reduce the probability of fracture of the contact surface and make the workpiece have higher mechanical properties.

[0069] In some specific embodiments, the second surface of the first structural layer is provided with a roughened structure, and the roughened structure is fused with the second structural layer to fasten the two.

[0070] In some specific embodiments, a surface of the second structural layer in contact with the first structural layer is provided with a roughened structure, and the roughened structure is fused with the second surface of the first structural layer to fasten the two.

[0071] In some specific embodiments, the texturing structure may be arranged in a single row or in multiple rows.

[0072] In some specific embodiments, the roughened structure may be one or more of needle-shaped burrs, conical burrs, round protrusions, columnar protrusions, and irregular protrusions.

[0073] In some specific embodiments, the height of the hairline structure is 0.001-0.002 mm.

[0074] In some specific embodiments, the second surface of the first structural layer and the side of the second structural layer in contact with the first structural layer are both provided with a roughened structure, in order to further increase the contact area and fasten the two.

[0075] When the second surface of the first structural layer and the side of the second structural layer in contact with the first structural layer are both provided with a roughened structure, the roughened structures may all be convex structures, or one side may be a convex structure and the other side may be a concave structure, or each side may be provided with a convex structure and a concave structure.

[0076] In some specific embodiments, the hairy structure of the first structural layer matches the hairy structure of the second structural layer, that is, the hairy structure of the first structural layer and the hairy structure of the second structural layer are arranged in a concave-convex manner.

[0077] In some specific embodiments, the hairy structure of the first structural layer and the hairy structure of the second structural layer are both convex structures, and the schematic diagram of the concave-convex matching structure of the two is as shown in FIG. Figure 3 shown.

[0078] In some specific embodiments, the textured structure of the first structural layer and the textured structure of the second structural layer are arranged as a convex structure and a concave structure arranged in sequence. Figure 4 shown.

[0079] In some specific embodiments of the present application, the surface of the hairy structure is a roughened surface, so as to further increase the contact surface and improve the fastening of the first structural layer and the second structural layer.

[0080] The above-mentioned hairy structure can also be called a micro-textured structure.

[0081] The above-mentioned roughened structures fuse and penetrate each other during the high-temperature hot rolling process, and an alloy layer is formed on the bonding surface, so that the formed appearance structural parts have higher mechanical properties and are not prone to fracture.

[0082] The above-mentioned appearance structural parts provided in this application can be used as product appearance.

[0083] Based on this, the present application provides an electronic device, including:

[0084] An appearance structural part, the appearance structural part comprises a first structural layer and a second structural layer, the first structural layer comprises a first surface and a second surface; the appearance of the first surface does not change after anodizing, and the second surface is in contact with and connected to a surface of the second structural layer;

[0085] ontology;

[0086] The appearance structural component wraps at least one surface of the body, and the first surface is an outer surface of the wrapped surface.

[0087] In order to further illustrate the present application, the appearance structural parts and the electronic device provided by the present application are described in detail below in combination with the embodiments.

[0088] The purity of the following recovered aluminum solution refers to: 100% - the mass content of impurities in the recovered aluminum material.

[0089] Example 1

[0090] The non-recoverable aluminum solution A and the recycled aluminum solution B are respectively cast in fixed containers to obtain substrates A and B. The substrate A has a width of 450 mm and a thickness of 200 mm, and the substrate B has a width of 450 mm and a thickness of 1000 mm.

[0091] The non-recoverable aluminum solution A is 5052.

[0092] The recovered aluminum solution is recovered 5052 with a purity of 80%.

[0093] Substrate A and substrate B are placed on a cleaning and degreasing unit for chemical degreasing treatment. A degreasing solution made of 5000 kg of water and 1400 kg of a degreasing agent is placed in the solution tank. The weight percentage concentration of the degreasing agent solution is 28%, the solution temperature is 80°C, the degreasing time is one minute, and the drying temperature is 90°C.

[0094] The chemically degreased substrate A and substrate B are placed on different machines for surface grinding. The grinding machine speed is 1200 rpm. The composite surface is completely ground to an appropriate grinding depth of 0.5 mm.

[0095] The polished substrate A and substrate B are sent to a hot composite rolling mill at a hot rolling temperature of 450° C. and are repeatedly hot rolled to a thickness of 0.6 to 0.8 mm.

[0096] The composite substrate A and substrate B (referred to as substrate A / B) are subjected to diffusion annealing to strengthen their bonding strength and achieve the effect of no stratification. The bell-shaped furnace is used for annealing. The protective gas in the furnace is a mixed gas decomposed from ammonia, that is, 75% hydrogen and 25% nitrogen, which protects the bright metal surface from oxidation and performs high hydrogen reduction on the surface oxide film. The gas flow is controlled at 40m 3 / hour, natural gas heating is adopted, diffusion annealing temperature is 450℃, holding time is 4 hours, aluminum molecules diffuse on the contact surface of substrate A and substrate B, alloy layer is formed on the bonding surface, slowly cooled to 60℃ and taken out of the furnace, tensile strength reaches 180MPa, elongation is 21%, aluminum surface hardness is HV70.

[0097] The above-mentioned diffusion annealed substrate A / B double-layer thermal composite material is leveled by a leveling machine to eliminate the material yield platform mark, ensure that the surface finish is greater than level 7, the leveling amount is 3%, the leveling force is 60 tons, and the speed is 20 meters / minute.

[0098] The flattened substrate A / B double-layer thermal composite material is subjected to a stretching and straightening treatment at a speed of 30 minutes / meter and an elongation controlled at 1.5%.

[0099] The above-mentioned straightened composite roll is cut into strips of fixed length according to requirements, and the cutting speed is 15 meters / minute.

[0100] In the final product, the thickness of substrate A is 0.1mm, the thickness of substrate B is 0.7mm, and the mass proportion of recycled materials is 87.5%.

[0101] The composite appearance parts were characterized by scanning electron microscopy. The surface grain characterization at 100 times showed that no defects were formed on the material surface. The longitudinal grain characterization at 100 times showed that substrates A and B were fused together to form a complete crystal structure.

[0102] The longitudinal and transverse 90° bending tests showed that no cracks were produced on the composite appearance parts.

[0103] The above shows that the two materials are successfully composited.

[0104] Example 2

[0105] The composite method is the same as Example 1, except that the non-recoverable aluminum solution A is silk aluminum 5L52, and the recovered aluminum solution is recovered silk aluminum 5L52 with a purity of 80%.

[0106] In the final product, the thickness of substrate A is 0.1mm, the thickness of substrate B is 0.5mm, and the mass proportion of recycled materials is 83.3%.

[0107] After testing, the mechanical properties and strength of the composite appearance parts meet the requirements, there are no defects on the surface, and substrates A and B are fused together to form a complete crystal structure.

[0108] No cracks were found in the longitudinal and transverse 90° bending tests.

[0109] Example 3

[0110] The composite method is the same as in Example 1, except that the non-recoverable aluminum solution A is a high-strength aluminum alloy 5H59, and the recovered aluminum solution is a recovered aluminum alloy 5H59 with a purity of 80%.

[0111] In the final product, the thickness of substrate A is 0.1mm, the thickness of substrate B is 0.5mm, and the mass proportion of recycled materials is 83.3%.

[0112] After testing, the mechanical properties and strength of the composite appearance parts meet the requirements, there are no defects on the surface, and substrates A and B are fused together to form a complete crystal structure.

[0113] No cracks were found in the longitudinal and transverse 90° bending tests.

[0114] Example 4

[0115] The composite method is the same as Example 1, except that the non-recoverable aluminum solution A is high-strength silk aluminum, and the recovered aluminum solution is recovered high-strength silk aluminum with a purity of 80%.

[0116] In the final product, the thickness of substrate A is 0.1mm, the thickness of substrate B is 0.5mm, and the mass proportion of recycled materials is 83.3%, breaking the current limit of 20% recycling rate of silk aluminum.

[0117] After testing, the mechanical properties and strength of the composite appearance parts meet the requirements, there are no defects on the surface, and substrates A and B are fused together to form a complete crystal structure.

[0118] No cracks were found in the longitudinal and transverse 90° bending tests.

[0119] The appearance structural parts provided in this application are completely integrated with different materials, and the ESG grade of metal products can exceed 80 without affecting the appearance.

[0120] The description of the above embodiments is only used to help understand the method and core idea of ​​the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. An appearance structural part, It is characterized in that comprising a first structural layer and a second structural layer; The first structural layer includes a first surface and a second surface; the appearance of the first surface does not change after anodizing; The second surface is in contact with and connected to a surface of the second structural layer.

2. The appearance structural member according to claim 1, It is characterized in that The first structural layer and the second structural layer are respectively made of aluminum alloy materials with different purities, and the material purity of the first structural layer is greater than the material purity of the second structural layer.

3. The appearance structural member according to claim 1, It is characterized in that The thickness of the first structural layer is 0.05-0.2 mm; The thickness of the second structural layer is 0.5-1.0 mm.

4. The appearance structural member according to claim 1, It is characterized in that An aluminum strip layer with a double-sided roughened structure is arranged between the first structural layer and the second structural layer; the roughened structure is fused with the first structural layer and the second structural layer respectively to fasten the two.

5. The appearance structural member according to claim 1, It is characterized in that The second surface of the first structural layer is provided with a roughened structure, and the roughened structure is fused with the second structural layer so that the two are fastened; Alternatively, a surface of the second structural layer in contact with the first structural layer is provided with a textured structure, and the textured structure is fused with the second surface of the first structural layer to fasten the two.

6. The appearance structural member according to claim 5, It is characterized in that The texturing structure is arranged in multiple rows.

7. The appearance structural member according to claim 5, It is characterized in that The roughened structure is one or more of needle-shaped burrs, conical burrs, round protrusions, columnar protrusions, and irregular protrusions.

8. The appearance structural member according to claim 5, It is characterized in that The height of the roughened structure is 0.001-0.002 mm.

9. The appearance structural member according to claim 5, It is characterized in that The surface of the hairy structure is a roughened surface.

10. An electronic device, It is characterized in that include: An appearance structural part, the appearance structural part comprises a first structural layer and a second structural layer, the first structural layer comprises a first surface and a second surface; the appearance of the first surface does not change after anodizing, and the second surface is in contact with and connected to a surface of the second structural layer; ontology; The appearance structural component wraps at least one surface of the body, and the first surface is an outer surface of the wrapped surface.